2004
DOI: 10.1158/1078-0432.ccr-04-0306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Inflammatory Breast Cancer

Abstract: Purpose: Inflammatory breast cancer (IBC) is a rare but particularly aggressive form of primary breast cancer. The molecular mechanisms responsible for IBC are largely unknown.Experimental Design: To obtain further insight into the molecular pathogenesis of IBC, we used real-time quantitative reverse transcription (RT)-PCR to quantify the mRNA expression of 538 selected genes in IBC relative to non-IBC.Results: Twenty-seven (5.0%) of the 538 genes were significantly up-regulated in IBC compared with non-IBC. N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
161
4
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(172 citation statements)
references
References 28 publications
5
161
4
2
Order By: Relevance
“…We found 181 genes which were 2-fold differentially changed. In other studies, IGFBP7 was screened in the microarray (25,26), which may be related with tumor metastasis. By identification and quantification of membrane proteins, network 2 (grouped by IPa) shows 12-related genes involved in the endocrine system, disorders, metabolic disease cell-to-cell signaling and interaction.…”
Section: Discussionmentioning
confidence: 99%
“…We found 181 genes which were 2-fold differentially changed. In other studies, IGFBP7 was screened in the microarray (25,26), which may be related with tumor metastasis. By identification and quantification of membrane proteins, network 2 (grouped by IPa) shows 12-related genes involved in the endocrine system, disorders, metabolic disease cell-to-cell signaling and interaction.…”
Section: Discussionmentioning
confidence: 99%
“…25 Tumor-derived CCL5 is detected in many clinical specimens of breast and cervical cancers; greater plasma levels in patients with progressive and more advanced disease than those in remission, [26][27][28] and it constitutes a prominent part of a poor prognosis signature of inflammatory BC. 29,30 An analysis of large core needle biopsies of 113 invasive breast carcinomas revealed that the concentration of CCL5 was significantly higher in the groups of patients with axillary lymph node metastasis than those without. 31 Most BC-derived cell lines spontaneously produce large amounts of CCL5, and the incidence of CCL5 expression detected in tissue sections of breast carcinomas is considerably higher than in normal duct epithelial cells or in those of benign breast lumps.…”
Section: Ccl5 and Human Breast Cancer (Bc)mentioning
confidence: 99%
“…In terms of breast cancer, a number of studies have suggested that RANTES is associated with breast malignancy. In patients with breast cancer, advanced disease, early relapse, and poor prognosis are significantly correlated with elevated RANTES expression levels in biopsy specimens and serum (26)(27)(28). Therefore, the precise role of RANTES signaling in breast cancer should be clarified.…”
Section: Introductionmentioning
confidence: 99%